Thyroid papillary carcinoma combined with primary follicular lymphoma: a case report - Ting Xu; Li Wu; Hua Ye; Shuai Luo; Jinjing Wang (BMC, 2024)
Abstract Background Papillary thyroid carcinoma (PTC) stands out as the most prevalent epithelial malignant thyroid tumor. Thyroid primary follicular lymphoma (PFL) represents a rare malignant tumor originating from mesenchymal tissues. The concurrent occurrence of PTC and PFL is exceptionally rare, particularly in the context of Hashimoto's thyroiditis, presenting significant challenges in clinical diagnosis and treatment. Case demonstration A 44-year-old female patient presented with a neck mass persisting for over 1 month. The patient underwent surgery, and the incised tissues were subjected to pathology examinations, along with immunohistochemistry and next-generation sequencing tests suggestive of an EZH2 gene mutation in the tumor cells. The final pathological diagnosis confirmed the presence of PTC combined with PFL. Following a 27-month follow-up, the patient displayed no signs of recurrence or metastasis. Conclusions The concurrent occurrence of PTC and PFL poses notable challenges in clinical practice, requiring careful consideration in diagnosis and treatment. Herein, we present a rare case of PTC combined with PFL featuring an EZH2 gene mutation, which can be easily overlooked in the context of Hashimoto's thyroiditis. The patient's favorable response to surgical and radiotherapeutic interventions underscores the importance of accurate diagnosis and tailored treatment strategies in similar cases.